2015
DOI: 10.1002/ece3.1670
|View full text |Cite
|
Sign up to set email alerts
|

A novel marine mesocosm facility to study global warming, water quality, and ocean acidification

Abstract: We describe a completely randomizable flow‐through outdoor mesocosm for climate change and ecotoxicology studies that was built with inexpensive materials. The 16 raceway tanks allow up to 6× water renewal per hour, avoiding changes in natural abiotic seawater conditions. We use an open‐source hardware board (Arduino) that was adapted to control heaters and an innovative CO 2 injection system. This system reduced seawater pH up to −0.9 units and increased temperature up to +6°C in three treatments and a contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Worldwide, so far only very few mesocosm systems were designed for replicated and longer‐term (> weeks to few months) studies on marine benthic systems in medium to large‐scale experimental units (> 500 L; partly reviewed in Stewart et al ; Wahl et al ). In the tropic and sub‐tropic zones, the SeaSim facility in the Australian Institute for Marine Sciences in Townsville, Queensland, Australia (https://www.aims.gov.au/seasim), the mesocosm facility at the South Australian Research and Development Institute (SARDI) Aquatic Sciences, West Beach, Australia (Falkenberg et al ), a mesocosm system on Hawaii (Jokiel et al ), the CRETACOSMOS at the Hellenic Centre for Marine Research in Greece, the Red Sea Simulator (Bellworthy and Fine ), or the Coral Vivo Project Research Station in Brazil (Duarte et al ), were established ‐ mainly for temperature and pH manipulations in either static or real‐time offset ((Duarte et al ); maintaining field variability) treatment approaches. Some of these systems can also expose organisms or communities to local environmental stressors such as nutrients or contaminants (Duarte et al ), or differing light conditions, salinity shifts, and/or sedimentation (SeaSim, Australia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Worldwide, so far only very few mesocosm systems were designed for replicated and longer‐term (> weeks to few months) studies on marine benthic systems in medium to large‐scale experimental units (> 500 L; partly reviewed in Stewart et al ; Wahl et al ). In the tropic and sub‐tropic zones, the SeaSim facility in the Australian Institute for Marine Sciences in Townsville, Queensland, Australia (https://www.aims.gov.au/seasim), the mesocosm facility at the South Australian Research and Development Institute (SARDI) Aquatic Sciences, West Beach, Australia (Falkenberg et al ), a mesocosm system on Hawaii (Jokiel et al ), the CRETACOSMOS at the Hellenic Centre for Marine Research in Greece, the Red Sea Simulator (Bellworthy and Fine ), or the Coral Vivo Project Research Station in Brazil (Duarte et al ), were established ‐ mainly for temperature and pH manipulations in either static or real‐time offset ((Duarte et al ); maintaining field variability) treatment approaches. Some of these systems can also expose organisms or communities to local environmental stressors such as nutrients or contaminants (Duarte et al ), or differing light conditions, salinity shifts, and/or sedimentation (SeaSim, Australia).…”
Section: Discussionmentioning
confidence: 99%
“…In the tropic and sub‐tropic zones, the SeaSim facility in the Australian Institute for Marine Sciences in Townsville, Queensland, Australia (https://www.aims.gov.au/seasim), the mesocosm facility at the South Australian Research and Development Institute (SARDI) Aquatic Sciences, West Beach, Australia (Falkenberg et al ), a mesocosm system on Hawaii (Jokiel et al ), the CRETACOSMOS at the Hellenic Centre for Marine Research in Greece, the Red Sea Simulator (Bellworthy and Fine ), or the Coral Vivo Project Research Station in Brazil (Duarte et al ), were established ‐ mainly for temperature and pH manipulations in either static or real‐time offset ((Duarte et al ); maintaining field variability) treatment approaches. Some of these systems can also expose organisms or communities to local environmental stressors such as nutrients or contaminants (Duarte et al ), or differing light conditions, salinity shifts, and/or sedimentation (SeaSim, Australia). In temperate latitudes, the Kiel Outdoor Benthocosms in the Baltic Sea (Wahl et al ) and the Sylt Benthic Mesocosm Facility (Pansch et al ) in the North Sea (Wadden Sea) were recently established, mainly testing temperature and acidification (partly eutrophication) effects on communities.…”
Section: Discussionmentioning
confidence: 99%
“…Control of the abiotic factors and the biotic responses based on the treatments applied is critical for mesocosm experiments (Duarte et al, ; Richmond, ). The present study showed that the experiments performed with the PROCORAIS Mesocosm achieved this control even in different configurations.…”
Section: Discussionmentioning
confidence: 99%
“…These additions have greatly simplified the user interface and human monitoring required and are therefore highly recommended inclusions for future mesocosm designs. Finally, the proximity of the facility to the natural reef not only simplifies sample collection and the infrastructure required for a flow-through system, but also helps to best as possible mimic abiotic field conditions, as realized by other existing systems (e.g., Jokiel et al 2014;Duarte et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Smaller individual experimental units in land-based flowthrough mesocosms give researchers continuous access and simplified husbandry, e.g., in the cases of Jokiel et al (2014) in Hawaii and of Falkenberg et al (Falkenberg et al 2016) in Australia. A marine mesocosm facility at the Coral Vivo Project Research Station in Brazil has high replication (48 tanks) of up to four temperatures and four pH treatments (Duarte et al 2015). Within this system, treatment conditions are set to a delta from reef water conditions, maintaining field variability.…”
mentioning
confidence: 99%